The sensitivity of ceramic gas sensor based on SnO2-Nb2O5-CuO system [microfilm] - Syahrul Humaidi (Skudai : Universiti Teknologi Malaysia, 2000)
Thesis (Master of Science (Physics)) - Universiti Teknologi Malaysia, 2000